Analysis of LKPD Development Needs Based on Problem Solving in Mobile Packet Tracer Application Utilization in Network Infrastructure Administration Subjects - Fadhilla Ulfa; Wakhinuddin S; Hansi Effendi (EDUTEC : Journal of Education And Technology, 2020)
Vocational schools are the education required to improve the 4C capabilities required in the 21st Century. This is because vocational school aims to produce ready-made graduates in the business world and industry. Therefore, it is important for students to improve their problem-solving skills, especially in terms of skills. Exercise is important, so even in distance learning, students still get a good practical experience. In the subjects of network infrastructure administration (AIJ) in the field of network computer engineering expertise (TKJ) the use of packet tracer mobile applications can be used as an alternative solution. Therefore, it is necessary to develop a problem solving-based worksheet (LKPD) to optimize the utilization of packet tracer media.